STUDY OF BEHAVIOUR BENDING CONCRETE BEAM FIBER PLASTIC BENESER COMPOSITES - Kurdian Suprapto (Journal of Civil Engineering, 2011)
“Fiber reinforced concrete” is made from cement, fine aggregate, coarse aggregate, water and many fibers that randomly spread within the mixture. To increase the ability of concrete to resist tensile and flexure, efforts are done by giving reinforcements or other material such as fibers in the tensile region.In this research the examination done in experiment with add plastic fibers of plastic benneser (poly-acrylonitryl styrene) in concrete mixture, with the percentage between 0% - 1, 00%.Otherwise in this research, the use of high concrete quality, are developing from the past research would have done in Unitomo. And the purpose of this research is to know the behavior of the mechanic phenomena like stretch and ductility from fibers concrete of beneser of higher concrete quality as united. So with this could be compare with the higher concrete quality without fibers. The concrete sample of fibers composite is made with three different things like: cylinders sample with size Ø10 and 15 cm high 20 and 30 cm, and block sample with size 15 X 20 X 60 cm. Cross section of full fibers composite and partial is used by block sample, only in stretch area below the neutral lines. The result says that: strengthened in splitting in a cylinder sample between 12, 56 – 27, 07 %, and the power of ductility from the block sample of full fibers between 12, 95 % – 20, 19 %, and the partial is 12 – 16, 57 %.